Re-examining traditional service quality in an e-banking era - Wong, David; Rexha, Nexhmi; Phau, Ian (Emerald Group Publishing Limited, 2008)
The paper re-examines the role of traditional service quality in an e-banking environment by providing a review of (a) how traditional service quality perceptions have evolved through the current and continuing stream of change in banking technology and (b) the corresponding changes in the nature of how banks interact with their customers. Data were collected from a mail survey sent out to a commercially purchased mailing list of 2,500 business names and addresses. The overall usable response rate was 30.6%. Quadrant analysis was performed on the service quality dimensions from the SERVQUAL scale. While the importance ranking of the five SERVQUAL dimensions have not changed dramatically over the years, large discrepancies were found between customer expectations and their perceived performance of traditional banking services. Quadrant analysis produced specific recommendations on how banks should prioritise the allocation of their resources to maintain high perceived service quality in their human interactions. This is the first study which revisits and re-examines traditional service quality in the e-banking era. It highlights how high levels of traditional service quality may lead to increased customer trust and thus more successful cross-selling of e-banking products to customers.